2020
DOI: 10.6065/apem.2020.25.1.52
|View full text |Cite
|
Sign up to set email alerts
|

Successful rapid weight reduction and the use of liraglutide for morbid obesity in adolescent Prader-Willi syndrome

Abstract: Prader-Willi syndrome (PWS), an imprinting disorder, results from the loss of expression of a paternal gene on chromosome 15q11-q13. Progressive obesity and its associated complications lead to increased morbidity and early death in PWS patients. The management techniques available for morbid obesity in adolescents and adults with PWS are limited. Herein, we report successful weight reduction in an adolescent PWS case showing morbid obesity and respiratory failure. An 18-year-old girl with PWS presented with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…Importantly, the authors did not observe BMI changes during the short term administration and suggested further studies with long‐term administration as follow up, as well a combination of exenatide with behavioural modifications 244 . Further, a more recent case report from Kim and colleagues demonstrated rapid and marked weight loss in a PWS adolescent (female, 18 years old) upon liraglutide (another GLP‐1R agonist) administration 245 . Remarkably, the effects of GLP‐1R activation modulate hypothalamic neuronal populations engaged in energy homeostasis 246 …”
Section: Conclusion and Future Prospectivementioning
confidence: 97%
See 1 more Smart Citation
“…Importantly, the authors did not observe BMI changes during the short term administration and suggested further studies with long‐term administration as follow up, as well a combination of exenatide with behavioural modifications 244 . Further, a more recent case report from Kim and colleagues demonstrated rapid and marked weight loss in a PWS adolescent (female, 18 years old) upon liraglutide (another GLP‐1R agonist) administration 245 . Remarkably, the effects of GLP‐1R activation modulate hypothalamic neuronal populations engaged in energy homeostasis 246 …”
Section: Conclusion and Future Prospectivementioning
confidence: 97%
“…244 Further, a more recent case report from Kim and colleagues demonstrated rapid and marked weight loss in a PWS adolescent (female, 18 years old) upon liraglutide (another GLP-1R agonist) administration. 245 Remarkably, the effects of GLP-1R activation modulate hypothalamic neuronal populations engaged in energy homeostasis. 246 Even though the therapeutic approach in PWS is still evolving, it is clear by now that hypothalamic dysfunction needs to be a key…”
Section: Con Clus I On and Future Pros Pec Tivementioning
confidence: 99%
“…There were six results for PWS and liraglutide, with four case reports meeting inclusion criteria. These included: a 17-year-old with PWS on liraglutide and metformin who had weight loss, increased satiety, as well as lower HbA1c and fasting glucose; an 18-year-old with PWS and dyspnea requiring mechanical ventilation due to severe obesity who maintained weight reduction on liraglutide; a 13-year-old with PWS and diabetes, with a decrease in glucose and HbA1c on liraglutide and empagliflozin; and a 19-year-old with PWS and diabetes who had improved glycemic control, HbA1c, insulin resistance, and weight loss on liraglutide and empagliflozin [ 21 , 24 , 25 , 26 , 27 ]. The remaining cases were focused on populations over the age limit or in a different language.…”
Section: Resultsmentioning
confidence: 99%
“…Less is known about the efficacy of GLP1-RA on syndromic obesity. To the best of our knowledge liraglutide effects on morbid obesity were described in 7 PWS patients all affected also by T2DM (15)(16)(17)(18) and in a prospective case-control nonrandomized study on 14 patients affected by monogenic obesity related to melanocortin-4 receptor (MC4R) mutations (19).…”
Section: Discussionmentioning
confidence: 99%